Hybrid Raman-erbium random fiber laser with a half open cavity assisted by artificially controlled backscattering fiber reflectors - R. A. Perez-Herrera (Nature Portfolio, 2021)
Abstract A hybrid Raman-erbium random fiber laser with a half-open cavity assisted by chirped artificially controlled backscattering fiber reflectors is presented. A combination of a 2.4 km-long dispersion compensating fiber with two highly erbium-doped fiber pieces of 5 m length were used as gain media. A single random laser emission line centered at 1553.8 nm with an optical signal to noise ratio of 47 dB were obtained when pumped at 37.5 dBm. A full width at half maximum of 1 nm and a 100% confidence level output power instability as low as 0.08 dB were measured. The utilization of the new laser cavity as a temperature and strain sensor is also experimentally studied.